The Impact of Environmental Accounting on Strategic Management Accounting: A Research on Manufacturing Companies - Tanc, Ahmet; Gokoglan, Kadir (International Journal of Economics and Financial Issues, 2015)
The aim of this study is investigating the sensitivity of manufacturing companies operating in the Organized Industrial Zone of Diyarbakır to environmental issues and environmental accounting approaches within the scope of social responsibility accounting as well as investigating the applicability of these concepts in the enterprises and as a result their impacts on strategic management accounting. According to the basic findings of the research and their responses to environmental accounting concepts and approaches, it is believed that enterprises applying environmental accounting get a competitive advantage and the added value of the company also increases as a result of the concept of social responsibility. Keywords: Environment Accounting; Environment Cost; Strategic Management Accounting JEL Classifications: M41; Q20; Q29